Perancangan Aplikasi Absensi Siswa Menggunakan Fingerprint Berbasis Web di SMK Insan Mulia - Aang Alim Murtopo; Zaenul Arif; M. Herly Rumambi (Yayasan Literasi Sains Indonesia, 2023)
Recording student attendance is a critical aspect in managing education at the Insan Mulia Vocational High School (SMK). Along with technological developments, designing student attendance applications using web-based fingerprint technology has become an effective solution for increasing accuracy and efficiency in the attendance process. This research aims to design a web-based student attendance application that utilizes fingerprint technology in the Insan Mulia Vocational School environment. The methodology used involves user needs analysis, study of related literature, as well as application design and development. This application was designed to meet the unique needs of Insan Mulia Vocational School, with a focus on ease of use, data security, and integration with the school's existing management system. The app's key features include student fingerprint registration, real-time attendance monitoring, attendance reports, and integration with school reporting systems. Data security is maintained through strong encryption and limited access based on user role. This application is implemented in a web environment so that it can be easily accessed by all stakeholders. It is hoped that the results of this research can make a positive contribution to the efficiency of managing student attendance at Insan Mulia Vocational School. In addition, it is hoped that this application can become a model for other schools in implementing fingerprint-based attendance technology to increase effectiveness and security in managing student attendance.